Cloze: An Authoring Tool for Teachers with Low Computer Proficiency - Hutchful, David; Mathur, Akhil; Joshi, Apurva; Cutrell, Ed (4th IEEE/ACM Conference on Information and Communication Technologies and International Development (ICTD) 2010, London, UK, IEEE, 2010)
The Multiple Mice project demonstrated the financial and learning benefits of enabling students in resource-constrained schools to share one computer. In India, the lack of Multiple Mice authoring tools coupled with teachers‘ low computer proficiency means little or no customized content is created. This is problematic as the capability to create digital content enables teachers to prepare digital lessons that address the particular learning needs of their students. In this paper, we report on a 34-week field study in three Indian peri-urban schools. We identify key issues impeding digital content creation by low computer proficiency teachers. We also present an authoring framework, Cloze, which successfully enables these teachers to create content for MultiPoint applications. Finally, we recommend guidelines for designing authoring tools for teachers with low computer proficiency.